Manajemen Pemberian Diet DASH (Dietary Approach to Stop Hypertension) dengan Penambahan Buah Kurma (Phoenix dactylifera L.) pada Penderita Hipertensi Kronis dalam Kondisi Puasa: Case Report - Adinda, Annida Azzah; Rahmawati, Ana Yuliah (Faculty of Medicine, Universitas Andalas, 2024)
The Diet Dietary Approach to Stop Hypertension (DASH) diet limits sodium and saturated fat and is high in fiber and minerals that can help control blood pressure. Date fruits are high in fiber and contain minerals and polyphenolic compounds that can lower blood pressure along with the DASH diet. This report is to observe the effect of DASH diet with date fruit combination on blood pressure changes in chronic hypertensive clients under fasting conditions. The study design was a single case study design to observe the effect of DASH diet combined with date fruit on hypertensive patients in fasting conditions. Subjects are patients undergoing homecare nutrition or diet programs by a nutritionist. The intervention was carried out for five days. The procedures include nutritional screening and assessment, diagnosis and nutritional care planning, implementation of nutritional care, and monitoring and evaluation. Data were analyzed through a descriptive approach to describe changes in blood pressure. Respondents' food intake during the intervention reached >80% of needs. Sodium intake was <1500 mg/day and fiber was>20 g/day. Blood pressure before the intervention showed grade I hypertension, while blood pressure on day 1 to day 5 of the intervention showed normal. The DASH diet combined with the provision of dates can support the reduction of blood pressure in patients with hypertension. Keywords: DASH Diet, date fruit, hypertension, fasting